Prevention and management of urinary tract infection: a non-antibiotic multi-modal approach - Faruqui, Arif A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Urinary tract infections (UTIs) are widespread, with 7 million outpatient visits, 1 million emergency department visits, and 100,000 hospitalizations annually. They mainly affect women aged 20-50. Although antibiotics are the main treatment, around 30% of treated women experience recurrence (rUTI). Regular antibiotic use also raises the risk of antibiotic resistance and side effects. Additionally, antibiotics can disrupt the intestinal and vaginal flora, increasing the risk of recurrence. Therefore, non-antibiotic treatments should be considered to reduce antibiotic use and side effects. Non-antibiotic options such as cranberry juice, D-mannose, probiotics, and potassium magnesium citrate can alleviate UTI symptoms and reduce recurrence risk. Research suggests that combining these non-antibiotic treatments, which work through different mechanisms, leads to better clinical outcomes. This review examines the role of each non-antibiotic treatment, the rationale for their combination, and supports their effectiveness with clinical evidence. Thus, the combination of non-antibiotic treatments may offer a better outcome in patients with UTI and rUTI.